Handbook on Spanish Civil Law adapted to Philippine Civil Code Obligations and Contracts - Albiez Dohrmann, Klaus Jochen; Castillo Parrilla, José Antonio (Ateneo de Manila University School of Law; University of the Philippines College of Law; University of the Philippines Law Center, 2023)
We are pleased to present this English translation of the book "Teoría general de obligaciones y contratos. Contratos en particular", by Professors Klaus Jochen Albiez Dohrmann and José Antonio Castillo Parrilla. We have chosen this handbook on obligations and contracts from among the different current handbooks available, as it is a comprehensive and accurate work that is completely up to date. Professors Albiez and Castillo offer a detailed analysis of Spanish law with constant reference to the Civil Code, case law, legal doctrine and, where relevant, European law. We considered it appropriate to divide this work into two volumes. The title of the first volume is "General Theory of Obligations and Contracts". It has its own special identity and contains the General Theory of Obligations and Contracts. The title of the second volume is "Contracts, Quasi-contracts and Non-contractual liability". It is devoted to the study of contracts in particular, quasi-contracts and non-contractual liability. In addition, we have adapted this Spanish Civil Law handbook to Philippine Civil Law. We therefore present this two-volume edition, which we hope will be of use to jurists and Law students.